2010
DOI: 10.1007/s12517-010-0147-9
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical survey for geological hazards assessment of Wadi Thuwal area, KSA: a case history

Abstract: Magnetic and seismic methods have been used in this study as complementary methods to each other to construct a geologic hazard map for Wadi Thuwal area. Magnetic interpretation for deep-seated geologic structures has involved reduction to pole algorithm and downward continuation techniques. It showed that there are three major fault trends: NE-SW and NNE-SSW, NW-SE, and N-S. Furthermore, shear zone has been found close to Harrat Thuwal, which was confirmed by the seismic method. Seismic method revealed three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…This earthquake activity can be taken as indicator for tectonic activity of some recorded fault trends through this zone. The previous geological and geophysical investigations have confirmed the presence of major NE-SW and NNE-SSW fault trends through Wadi Thuwal area (Al-Garni et al [3]; Al-Garni and El-Kaliouby [2]). In addition, evidences of shear zones are observed close to Harrat Thuwal (Al-Garni and Gobashy 2009).…”
Section: Thuwal-rabegh Zonementioning
confidence: 72%
See 1 more Smart Citation
“…This earthquake activity can be taken as indicator for tectonic activity of some recorded fault trends through this zone. The previous geological and geophysical investigations have confirmed the presence of major NE-SW and NNE-SSW fault trends through Wadi Thuwal area (Al-Garni et al [3]; Al-Garni and El-Kaliouby [2]). In addition, evidences of shear zones are observed close to Harrat Thuwal (Al-Garni and Gobashy 2009).…”
Section: Thuwal-rabegh Zonementioning
confidence: 72%
“…Depending on the distribution of earthquakes, fault parameters (strike and dip) of the major structural trend, seismicity parameters (a-and b-values, Table 1) and previous geological and geophysical studies (Alwash and Zakir [4]; Al-Qarni [5]; Al-Garni et al [3]; Al-Garni and El-Kaliouby [2]), five seismogenic source zones have been identified (Fig. 7).…”
Section: Seismotectonic Zonesmentioning
confidence: 99%
“…It is implemented in many integrated studies aiming to delineate the structural setting (e.g. Abdelazeem et al, 2021;Araffa et al, 2021;Azeem et al, 2014;Al-Garni et al, 2012) and in groundwater studies (Gobashy et al, 2021b;Al-Garni et al, 2006) and exploration of the mineral (Gobashy et al, 2022;Gobashy et al, 2020;Gobashy et al, 2021a;Abdelrahman et al, 2019), groundwater contamination (Rehman et al, 2019).…”
Section: Magnetic Methodsmentioning
confidence: 99%
“…It is employed as an effective technique and has numerous geological uses, such as geologic mapping of potential locations with buried igneous bodies that are frequently linked with mineralization, identifying supra-basement features, and estimating the thickness of sedimentary cover 12 . Moreover, it is also the favourite for studying the tectonic structure, identification of intra-basement faults and uplifts, basin modelling, and structural geometry 13 16 , petroleum exploration modelling of geothermal and groundwater resources 17 19 , allowing the visualization of the geological structure of the upper crust, like faults, aids in the discovery of buried objects such as pipes, drums, and unexploded ordnance 20 . Furthermore, it aids in mineral exploration 13 , 16 , 18 , 21 – 30 .…”
Section: Introductionmentioning
confidence: 99%